Buddhist Constitutionalism in Thailand: When Rājadhammā Supersedes the Constitution. Issue 2 (25th October 2018) - MÉRIEAU, Eugénie
Abstract: This article adds nuance to the classical account depicting Thailand as a secularized country by documenting how Buddhism informs constitutional thought and practices in contemporary Thailand. Throughout the twentieth century, Buddhist discourses have been used to bypass constitutional provisions in the name of 'dhamma' through the reliance on the rediscovery of the doctrine of the dhammarāja (the righteous King). In the early twenty-first century, a second rebirth of the discourse of the dhammarāja led to a further devaluation of the constitution as the supreme norm. The principles of a righteous King ( totsapitrājadhammā) were reconceptualized as a functional equivalent to constitutionalism – as constraining the King's power. This article first examines how modern lawyers used Buddhism as the vehicle to import Western constitutional ideas into the Siamese polity while reconstructing them as part of a royal legacy through the doctrine of the Ten Royal Virtues. It then turns to an analysis of the ever-increasing enshrinement of Buddhism in successive Thai constitutions since 1932. It concludes with an account of the politicization of the righteous King doctrine and its impact on constitutional practices.